PERBEDAAN TINGKAT DEHIDRASI, TEKANAN DARAH, DAN GANGGUANKESEHATAN PADA PEKERJA TERPAPAR IKLIM KERJA PANAS DI ATASDAN DI BAWAH NAB PADA BAGIAN PRODUKSI PT ISKANDAR INDAHPRINTING TEXTILE SURAKARTA - Wildan Hidayatullah, Arief; , Tarwaka, PGDip., Sc., M.Erg; , Sri Darnoto, SKM, M.PH (2016)
A hot working climate was the leading cause to excretion of body fluids through sweating which would eventually drives to dehydration and another health problems. The purpose of this study was to determine the difference among the rate of dehydration, blood pressure and health problems of workers exposed to hot working climate above and below NAB on production departement at PT. Iskandar Indah Printing Textile Surakarta. This research method used observational design with cross-sectional approach. The population in this study was production departement workers at PT. Iskandar Indah Printing Textile Surakarta which include Sizing and Weaving sections with totaling 61 people. The sampling technique used in this research was purposive sampling with the number of samples that met the inclusion criteria as many as 34 people. The statistical test used in this research was the Mann-Whitney U. The statistical result of this study on the different levels of dehydration, blood pressure and health problems of workers exposed to hot working climate above and below NAB, the three differ significantly (p=0,000). From this result, it can be concluded that there are differences in the level of dehydration, blood pressure and health problems among workers exposed to the hot working environment above and below NAB.